2015
DOI: 10.1088/0953-4075/48/12/125101
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific formation of metastable OCS2+studied by Auger-electron-ion coincidence method

Abstract: We have studied the site-specific formation of metastable OCS 2+ in the C1s and the O1s Auger decays of OCS molecules by using an Auger-electron-ion coincidence technique. The coincidence measurement reveals the metastable character of the Auger final states with the (3π) −2 configuration. The formation of metastable OCS 2+ is observed negligibly in the C1s Auger decay and only weakly in the O1s Auger decay, in contrast to the favorable metastable formation previously reported for S2p Auger decay. It is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The double ionization potential of OCS at the equilibrium structure (Franck-Condon region), reached by removing two valence electrons from the 3π orbital, is 30.3 eV (Langford et al, 1991). Since the electronic ground state of OCS 2+ is the metastable X 3 Σ − state (Kaneyasu et al, 2015) and its lifetime is theoretically predicted to be on the order of 10 160 s (Ridard et al, 1988), the dissociation does not occur directly from the ground state of OCS 2+ . In our nuclear dynamics simulation in intense laser fields, dissociation from the (3π) −2 states does not occur within our simulation time.…”
Section: Resultsmentioning
confidence: 99%
“…The double ionization potential of OCS at the equilibrium structure (Franck-Condon region), reached by removing two valence electrons from the 3π orbital, is 30.3 eV (Langford et al, 1991). Since the electronic ground state of OCS 2+ is the metastable X 3 Σ − state (Kaneyasu et al, 2015) and its lifetime is theoretically predicted to be on the order of 10 160 s (Ridard et al, 1988), the dissociation does not occur directly from the ground state of OCS 2+ . In our nuclear dynamics simulation in intense laser fields, dissociation from the (3π) −2 states does not occur within our simulation time.…”
Section: Resultsmentioning
confidence: 99%
“…Morse et al , 3 using well-resolved single-electron–ion coincidences (ei) also found that all CO + ions formed at ionization energies above 32 eV are in the form of CO + + S + ion pairs. Kaneyasu et al 24 using Auger electron–ion coincidences state in the text that the onset of the CO + + S + ion pair is at 34 eV, but their Fig. 3, from which this value is taken, clearly shows a weaker onset at 32 eV.…”
Section: Resultsmentioning
confidence: 92%
“…[6][7][8][9] For double ionization our knowledge of the fates of nascent OCS 2+ ions formed by various means is extensive. Studies have included direct ionization by single photons, 3,[10][11][12][13][14][15][16] electron [17][18][19] and ion impacts, 20,21 indirect ionization by Auger processes, [22][23][24][25][26][27][28] double-charge-transfer 29,30 and recently strong-field ultrafast laser interaction-induced multiple ionization. [31][32][33][34][35][36][37][38][39] The interpretation of the experimental work has been aided by extensive calculations of the state manifold [40][41][42][43][44][45] and possible dication dissociation pathways or by performing real-time time-dependent density functional theory (rtTDDFT) and semi-classical surfacehopping dynamics.…”
Section: Introductionmentioning
confidence: 99%